Legitimation: License for Registration of Interreligious Marriages by the State Court - Desmal Fajri (Activa Yuris: Jurnal Hukum, 2023)
The Surabaya District Court judge has granted the application for a permit to register an interfaith marriage between Rizal Adikara (Islam) and Eka Debora Sidauruk (Christian with decision Number: 916/Pdt.P/2022/PN.Sby. Previously, the registration of their marriage was rejected by the Population and Civil Registry Office. Civil Registry.The purpose of this research is to analyze judges' considerations in determining permission to register interfaith marriages.This type of research is library research, using a juridical normative approach.The source of data comes from primary legal materials, namely statutory regulations and legal materials secondary such as legal opinion/doctrine/theories from legal literature, research results, journals, papers, theses and websites related to research.This research is descriptive analytical in nature.Results of the research are that District Court judges have legitimized the registration of interfaith marriages with the consideration that The Marriage Law and the Law on Population Administration have provided space for the Court to render decisions and citizens have the right to defend their religious beliefs when they want to build a household. This judge has used a judicial activism approach in order to guarantee the freedom of citizens as protected by the constitution. Then this decision only granted permission to register religious marriages, not permission to carry out marriages because the applicant parties were married before the Court's decision